2012
DOI: 10.1002/cvde.201106919
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐Pulsed CVD for Film Growth in the CuNiN System

Abstract: A new ternary solid solution, Cu 3-x Ni xþy N, is prepared by gas-pulsed CVD at 260 8C. Gas pulses of the precursor mixtures Cu(hfac) 2 þ NH 3 and Ni(thd) 2 þ NH 3 , separated by intermittent ammonia pulses, are employed for the deposition of Cu 3 N and Ni 3 N, respectively. A few monolayers of the nitrides are grown in each CVD pulse and then mixed by diffusion to produce the solid solution. The metal content of the solid solution can be varied continuously from 100% to about 20% Cu, which means that the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…The strong growth rate dependence of ammonia on the other hand would indicate a blocking of the surface by the ligands of the metal precursor or by ligand fragments which have a low reactivity against gas phase NH 3 and -NH x surface species. These observations are in line with what has been observed previously for ALD of NiO from Ni(thd) 2 and water precursors where it was also found that large excess of water was needed for saturation (19). The differences in reaction order for the two precursors at the two temperatures indicates different reactions for the The microstructure of the initially formed crystallites for a deposition temperature of 230°C is depicted in fig 4 A-C.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The strong growth rate dependence of ammonia on the other hand would indicate a blocking of the surface by the ligands of the metal precursor or by ligand fragments which have a low reactivity against gas phase NH 3 and -NH x surface species. These observations are in line with what has been observed previously for ALD of NiO from Ni(thd) 2 and water precursors where it was also found that large excess of water was needed for saturation (19). The differences in reaction order for the two precursors at the two temperatures indicates different reactions for the The microstructure of the initially formed crystallites for a deposition temperature of 230°C is depicted in fig 4 A-C.…”
Section: Resultssupporting
confidence: 89%
“…The requirement for the metal precursor for Ni 3 N CVD is due to the metastable nature of the deposit and a high reactivity against both -NH x as well as atomic hydrogen at reasonable low temperatures is needed. Surface -NH x are expected to react in a similar way as -OH groups which are known to react with the bis(2,2,6,6-tetramethyl-3,5-heptanedionato)Ni(II) (Ni(thd) 2 ) precursor to produce NiO (19,20). Also the similar Cu(thd) 2 precursor is known to react with surface hydrogen on metallic surfaces (21).…”
Section: Introductionmentioning
confidence: 97%
“…Time-resolved precursor delivery can also be used to deposit thin films of ternary or quaternary materials. By combining known CVD and ALD chemistries for Cu 3 N and Ni 3 N in a sequential manner separated by NH 3 pulses a ternary solid solution of Cu 3‑x Ni x+y N can be deposited . In contrast, no deposition at all was obtained when using a nonpulsed CVD approach where all precursors were mixed together.…”
Section: Time-resolved Precursor Supply In Cvdmentioning
confidence: 99%
“…By combining known CVD and ALD chemistries for Cu 3 N and Ni 3 N in a sequential manner separated by NH 3 pulses a ternary solid solution of Cu 3-x Ni x+y N can be deposited. 15 In contrast, no deposition at all was obtained when using a nonpulsed CVD approach where all precursors were mixed together. This is speculated to be due to mutual blocking of the surface chemical reactions by the ligands or fragments of the ligands of the metal precursors; Cu(hfac) 2 and Ni(thd) 2 .…”
Section: ■ Introductionmentioning
confidence: 99%